2012
DOI: 10.1021/nl303501t
|View full text |Cite
|
Sign up to set email alerts
|

Solid–Solution Semiconductor Nanowires in Pseudobinary Systems

Abstract: Pseudobinary solid-solution semiconductor nanowires made of (GaP)(1-x)(ZnS)(x), (ZnS)(1-x)(GaP)(x) and (GaN)(1-x)(ZnO)(x) were synthesized based on an elaborative compositional, structural, and synthetic designs. Using analytical high-resolution transmission electron microscopy (HRTEM) and energy dispersive X-ray spectroscopy (EDS), we confirmed that the structure uniformity and a lattice match between the two constituting binary components play the key roles in the formation of quaternary solid-solution nanos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 25 publications
0
52
1
Order By: Relevance
“…To examine the correlation between band gap and composition, other synthetic methods to make bulk (Ga 1Àx Zn x )(N 1Àx O x ) have been explored. [33][34][35][36] As described in our previous report, 32 single crystalline (Ga 1Àx Zn x )(N 1Àx O x ) nanoparticles with diameters of $18 nm and x ranging from 0.30 to 0.87 can be obtained by exposure of a mixture of ZnO and ZnGa 2 O 4 nanocrystals to NH 3 at 650 C. The x value here refers to the overall molar composition of the sample usually measured by elemental analysis of the metal content, i.e., x ¼ Zn/(Zn + Ga). The earliest reported methods included nanowires as well as $10 nm nanoparticles with a range of x values from 0.08 to 0.48.…”
Section: Introductionmentioning
confidence: 99%
“…To examine the correlation between band gap and composition, other synthetic methods to make bulk (Ga 1Àx Zn x )(N 1Àx O x ) have been explored. [33][34][35][36] As described in our previous report, 32 single crystalline (Ga 1Àx Zn x )(N 1Àx O x ) nanoparticles with diameters of $18 nm and x ranging from 0.30 to 0.87 can be obtained by exposure of a mixture of ZnO and ZnGa 2 O 4 nanocrystals to NH 3 at 650 C. The x value here refers to the overall molar composition of the sample usually measured by elemental analysis of the metal content, i.e., x ¼ Zn/(Zn + Ga). The earliest reported methods included nanowires as well as $10 nm nanoparticles with a range of x values from 0.08 to 0.48.…”
Section: Introductionmentioning
confidence: 99%
“…For intrinsic semiconductors, the optical and electrical properties such as conductivity type, carrier density, and mobility, as well as the band structure, are usually confined subjected to their own nature . The electrical conductivity of semiconductors shows a strong impact on the integration of photoelectricity and electrical devices . Good examples in this context are field effect transistor and light emitting diode (LED).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, this replacement occurs randomly and often incompletely. The growth conditions of a homogeneous crystallization of such solid‐solutions are strictly confined to a local equilibrium . Even slight deviations in composition or temperature will result in a phase separation or might cause the formation of core–shell structures .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu et al reported the synthesis of (GaP) 1−x (ZnS) x NWs at a composition x = 0.045 and 0.968. 32 The Pan group have reported (GaAs) 1−x (ZnSe) x NWs with compositions in the range of x < 0.5. 33…”
mentioning
confidence: 99%